Visits Of Tourist On The English Interaction Skills Of The Community - Asty, Herfyna (JUPE : Jurnal Pendidikan Mandala, 2025)
Tourist Visits on the English Interaction Skills of the Community especially Tour Guides. This Research uses a qualitative approach with a case study method. The subjects in the study were five people at Village, especially. The instruments used were semi- structured interviews and audio recording evidence as supporting instruments. The results showed that are many impacts caused by tourist visits, both positive and negative impacts. Positive impacts such as increasing vocabulary in English, English pronounciation is getting clearer, and confidence in speaking English is increasing. The Negative impacts include cultural differences and miunderstanding when interacting with tourist using English,